ACUTE EFFECT OF FORMALIN ON PULMONARY FUNCTION TESTS IN MEDICAL STUDENTS - Binawara, Bijendra Kumar; ., Rajnee; S, Choudhary; KC, Mathur; H, Sharma; K, Goyal (Pakistan Journal of Physiology, 2010)
Background and Methods: The incessant complaints from medical students during and after gross anatomy dissections led to this study. The present study was carried out on 80 healthy (male) first year medical student’s between the age of 18–23 years. The pulmonary function tests included were FVC, FEV1, FEV1/FVC, FEF25–75% and PEFR carried out by computerised spirometer. All these parameters helped in evaluating pulmonary functions among medical students exposed to formaldehyde for two hours during their Anatomy dissection. Result: The study revealed statistically highly significant (p<0.0001) decrease in values of FVC, FEV1 and PEFR after exposure but reverted back to normal within 24 hrs. But FEV1/FVC ratio and FEF25–75% did not show any significant change. Conclusion: Medical students’ exposure to formalin during anatomy dissection is indeed hazardous to their health. Medical colleges should take more concrete measures to reduce students’ exposure to formalin.